Quantifying the influence of supplier relationship management and supply chain performance: an investigation of Bangladesh’s manufacturing and service sectors - Emon, Md Mehedi Hasan; Khan, Tahsina; Siam, Saleh Ahmed Jalal (Brazilian Journal of Operations & Production Management, 2024)
Purpose: This study explores the impact of Supplier Relationship Management (SRM) practices on supply chain performance, with a focus on cost efficiency, within the dynamic context of Bangladesh. The purpose is to elucidate the relationships between SRM practices, specifically Supplier Collaboration, Supplier Development, Supplier Evaluation and Selection, and Long-Term Supplier Relationships, and their influence on cost efficiency within supply chains. Design/Methodology/Approach: A quantitative research approach was employed, utilizing regression analysis and correlation analysis to analyze data collected through a structured survey from 270 Participants within Bangladesh’s Manufacturing and Service Sectors. The research adopted a cross-sectional time horizon, providing a snapshot view of the relationships between SRM practices and cost efficiency. Findings: The findings reveal that Supplier Collaboration and Long-Term Supplier Relationships significantly and positively influence cost efficiency within the supply chains of Bangladeshi organizations. These SRM practices collectively contribute to approximately 64.2% of the variance in cost efficiency, emphasizing their critical role in optimizing supply chain performance. Research Limitations/Implications: Limitations of this study include its cross-sectional nature and the focus on a specific set of SRM practices. Future research can explore additional SRM dimensions and employ longitudinal approaches for deeper insights. Practical Implications: Practitioners can leverage the study's findings to enhance supply chain performance by implementing holistic SRM strategies, fostering collaborative supplier relationships, and nurturing long-term partnerships with suppliers. Social Implications: This research contributes to the broader economic landscape of Bangladesh by highlighting the importance of SRM practices in enhancing cost efficiency, which can ultimately lead to economic growth and competitiveness. Originality/Value: This study extends the understanding of SRM practices by examining their applicability and significance in an emerging market like Bangladesh. It underscores the originality and value of SRM as a strategic imperative for organizations operating in diverse contexts.